Habitats Show More Impacts Than Host Species in Shaping Gut Microbiota of Sympatric Rodent Species in a Fragmented Forest - Teng, Yuwei; Yang, Xifu; Li, Guoliang; Zhu, Yunlong; Zhang, Zhibin (Frontiers in Microbiology, 2022)
Gut microbiota plays a significant role for animals to adapt to the changing environment. Host species and habitats are key drivers in shaping the diversity and composition of the microbiota, but the determinants of composition of the sympatric host gut microbiome remain poorly understood within an ecosystem. In this study, we examined the effects of habitats of different succession stages and host species on the diversity and composition of fecal gut microbiota in four sympatric rodent species (Apodemus draco, Leopoldamys edwardsi, Niviventer confucianus and N. fulvescens) in a subtropical forest. We found, as compared to the differences between species, habitat types showed a much larger effect on the gut microbiota of rodents. Alpha diversity of the microbial community of A. draco, N. fulvescens, N. confucianus was highest in farmland, followed by primary forest and shrubland, and lowest in secondary forest. Beta diversity of the three rodent species showed significant different among habitats. The alpha diversity of gut microbiota of L. edwardsi was significantly higher than those of A. draco and N. confucianus, and its beta diversity showed significant difference from A. draco. Our results suggested that gut microbiota was important for animals in responding to diet changes in different habitats under human disturbances.